Membangun Etika Profesi Akuntan Publik dari Sudut Pandang Maqasid Al-Shariah - Mitha Afik Valery Putri; Erfan Muhammad; Fitri Ahmad Kurniawan (Jurnal Ekonomi Syariah Pelita Bangsa, 2023)
This study aims to develop the concept of applying maqasid shariah and Islamic values ​​in order to improve the ethics of the public accounting profession. This study uses a qualitative method with a critical paradigm approach to social phenomena with various problems of violating the code of ethics of the accounting profession from the point of view of maqasid shariah and Islamic values. The result of this study is that improving the ethics of the public accounting profession in terms of maqasid shariah will result in protection of religion (Ad-Diin), namely help in goodness and piety. Protection of the soul (An-Nafs) is reflected in maintaining client confidentiality. Protection of Intellect (Al-Aql) is reflected in maintaining the continuity of the AP profession. Protection of descendants (An Nasb) is reflected in the acquisition of property in a lawful and thayyib way for the AP family. Protection of assets (Al-Maal) is reflected in the existence of financial statement accountability in a worldly and ukhrawi manner.